(untitled) (Research, Society and Development, 2022)
In recent years, the notions of artificial intelligence and emotional intelligence have grown in popularity in the relevant literature. The development of technology, particularly in the area of artificial intelligence, has made it possible to examine the numerous facets of human emotional behaviour in new and powerful ways. This article constitutes a narrative review in which we try to investigate the causal connection between emotional intelligence and artificial intelligence by using the most recently studies as well as studies from the last decade. It aims to determine whether AI systems possess several intelligence types similar to those seen in humans and whether these types can elicit various emotions in individuals. For this purpose we abstract the denotation of Emotional and Artificial intelligence at first and display the main human intelligence types such as the artificial types as well, according to the scientists. Thus, we exhibit the disciplines and the ways that these two intelligence areas are affected and how AI could be more useful for individual’s lifelong progress.